Doctor Sleep [videorecording (DVD)] - Flanagan, Mike, 1978-; Flanagan, Mike, 1978-; McGregor, Ewan, 1971-; Curran, Kyliegh, 2005-; Ferguson, Rebecca, 1983-; King, Stephen, 1947- (Warner Bros. Home Entertainment, 2020)
Dan Torrance remains traumatized by the sinister events that occurred at the Overlook Hotel when he was a child, spending his days self-medicating away the 'shine' with alcohol. His hope for a peaceful existence soon becomes shattered when he meets Abra, a teen who shares his extrasensory gift. Together, they form an unlikely alliance to battle the True Knot, a cult whose members try to feed off the shine of innocents to become immortal.